HUMOR IN BRITISH TELEVISION SERIES MIND YOUR LANGUAGE SEASON 1 - Muhammad Ihsan; Catur Kepirianto (Department of Linguistics, Faculty of Humanities, Diponegoro University, 2021)
Ambiguity in language is often considered as a problem. Ambiguity can be found in every aspect of language whether it is written or spoken text. Research in terms of ambiguity was normally found in written language, but this study conducted in spoken text. In this research, the ambiguity is spoken by non-native English in a humoristic expression. Lexical ambiguity is usually caused by homonymy and polysemy. This research aims to describe the ambiguity in the British television series Mind Your Language Season 1 and focus on the lexical ambiguity especially in polysemy and contextual meaning. The technique of collecting the data is note-taking technique. The writer describes all possible meanings from the ambiguous joke by analyzing the contextual meaning. This study is conducted to describe all possible meanings from the ambiguous jokes within the context. There are four contextual meanings in polysemy but the author focused on two contextual meaning that are mostly found in this study. By analyzing the contextual meaning, the writer reveals the correct interpretation and intention of the ambiguous words and mostly found type of contextual meaning in polysemy used by non-native English.Keywords: ambiguity, contextual meaning, lexical ambiguity, polysemy